2018
DOI: 10.1111/evo.13503
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic disparity of the elbow joint in domestic dogs and wild carnivores*

Abstract: In this article, I use geometric morphometrics in 2D from a sample of 366 elbow joints to quantify phenotypic disparity in domestic dog breeds, in wild canids, and across the order Carnivora. The elbow joint is a well-established morphological indicator of forearm motion and, by extension, of functional adaptations toward locomotor or predatory behavior in living carnivores. The study of the elbow joint in domestic dogs allows the exploration of potential convergences between (i) pursuit predators and fast-run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…This discrepancy could lead to misinterpretation of RT angle data and might not reflect the true torsional profile of each breed. However, the current literature, although limited, does not support significant variation in the RT angle between breeds …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This discrepancy could lead to misinterpretation of RT angle data and might not reflect the true torsional profile of each breed. However, the current literature, although limited, does not support significant variation in the RT angle between breeds …”
Section: Discussionmentioning
confidence: 67%
“…However, the current literature, although limited, does not support significant variation in the RT angle between breeds. 32,35,40,55,56 The fact that all animals in the study group exhibited distinguishable clinical, radiographic, CT, and, in most cases, arthroscopic data clearly identifying them as diseased exposes this study to selection bias. Because the landmarks for the proximal reference line lie in the same plane as the coronoid process, blinding the observers to the disease status of each individual was not possible, potentially exposing the study to test reviewer bias.…”
Section: Discussionmentioning
confidence: 99%
“…In the elbow joint, morphometric differences exist between breeds, and between different Canidae species based on their way of sourcing food. 30 Although there are currently no data available on differences in joint kinematics and kinetics in the specific breeds used in this study, the differences in subchondral bone density distribution indicate potential differences in joint loading patterns. The relationship between differences in loading pattern, locomotion and orthopaedic pathology remains subject to further research.…”
Section: Discussionmentioning
confidence: 90%
“…Morphometric studies in the elbow joint of carnivores have shown differences in joint anatomy linked to hunting methods. 30,31 Additionally, the grey wolf and the golden jackal were evaluated. The latter was included as the species that is a close relative to the domesticated dog, despite marked size differences.…”
Section: Introductionmentioning
confidence: 99%
“…The elbow joint can be used as a proxy to distinguish whether a carnivore hunts using a stalk-and-ambush strategy or by pursuing its prey. Here, Figueirido (2018) assesses whether elbow joint phenotypic disparity in domestic dogs exceeds that seen in wild carnivores, as has previously been found to be true for the * This article corresponds to Figueirido, B. 2018 skull (Wayne 1986).…”
mentioning
confidence: 99%